Dehumanization in Attack On Titan - Vanessa Cicilia Halim; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Manga is a Japanese comic that has its own genres, one of the most famous is shōnen. Attack on Titan is one of the most popular shōnen manga in the world, with a science fiction theme. Through this study, we want to analyze the dehumanization in the manga series by Hajime Isayama. We want to find out what forms of dehumanization occur and the reasons why the dehumanization happens to the victims, the Eldians. We use the theory of animalistic and mechanistic dehumanization to identify the forms of dehumanization in the manga. In addition, we also use the theory that state power increases dehumanization to find out the reasons that dehumanization happens. Based on our analysis results, victims treated like animals do not have human rights, are considered low class, and get persecuted. Victims treated like objects are considered "tools" to achieve goals, something that can be exchanged or destroyed, and ignores the victim's feelings. Meanwhile, the Eldians get dehumanized because they feel powerless and are considered a potential threat by the dehumanizers. It shows that dehumanization is a negative phenomenon that occurs due to differences.